The Effect of a Combined Training Program with Fenugreek and Green Cumin Supplementation on the Levels of Certain Inflammatory and Anti-Inflammatory Adipokines in Overweight Women - Lotfi , Hoora; Banaei Borojeni, Jamshid; Keshavarz, Saeed; Eftekhari , Elham (Health Nexus, 2025)
Obesity in older adults can lead to numerous health problems, including cardiovascular diseases, diabetes, hypertension, and a reduced quality of life. These issues are exacerbated by decreased physical activity and metabolic changes associated with aging. Weight management in older adults is of great importance, as it can help prevent these health issues. Additionally, weight control can contribute to maintaining independence and improving the quality of life in older adults. Therefore, this study aimed to investigate the effect of a combined training program with fenugreek and green cumin supplementation on the levels of certain inflammatory and anti-inflammatory adipokines in overweight women. In a quasi-experimental study, 60 overweight older women were randomly assigned to six groups: combined training/placebo (n=16), fenugreek supplement (n=16), green cumin supplement (n=16), combined training/fenugreek supplement (n=16), combined training/green cumin supplement (n=16), and control (n=16). Participants performed the combined training protocol for 8 weeks, with three sessions per week. The fenugreek supplement group consumed two capsules of 335 mg daily, while the green cumin supplement group consumed two capsules of 25 mg daily. The results indicated that in the combined training/placebo (P<0.001), green cumin supplement (P<0.001), combined training/fenugreek supplement (P<0.001), and combined training/green cumin supplement (P<0.001) groups, the mean differences in resistin and visfatin levels between pre-test and post-test were significant (P<0.05). All four groups resulted in a reduction in inflammatory and anti-inflammatory adipokine levels. In the fenugreek supplement and control groups, no significant differences were found between pre-test and post-test mean values (P>0.05). Furthermore, post-hoc test results showed a significant difference in the combined training/green cumin supplement group compared to the other four experimental groups, with a significantly greater reduction observed (P<0.001).